Spinal Cord Stimulation for the Treatment of Failed Neck Surgery Syndrome: Outcome of a Prospective Case Series. Issue 5 (22nd March 2018) - Hunter, Corey W.; Carlson, Jonathan; Yang, Ajax; Deer, Timothy
Abstract : Objectives: Spinal cord stimulation (SCS) is an accepted, cost‐effective treatment option for a variety of chronic pain syndromes, including failed back surgery syndrome (FBSS). The application of SCS in the cervical spine, particularly for pain after cervical spine surgery, has been drawn into question in recent years by payers due to a purported lack of clinical evidence. To challenge this claim, we analyzed data from a prospective registry to support the use of SCS in the cervical spine for pain after spine surgery. Materials and Methods: Data from the EMPOWER and PAIN registries were analyzed on patients diagnosed with pain after neck surgery (C‐FBSS) for the following outcomes: patient reported percent pain relief (PRPR), pain disability index (PDI), quality of life (QoL), and satisfaction at 3‐, 6‐, and 12‐month post‐implantation. Statistical analysis was provided for all measures. Results: Fifteen patients with C‐FBSS were successfully implanted with SCS leads in the cervical spine. PRPR was 65.2%, 62.4%, and 71.9% at 3‐, 6‐, and 12‐month post‐implantation, respectively. PDI scores were significantly reduced from baseline (51.21–23.70 at 12 months, p  = 0.001). At one‐year post‐implantation, the average overall QoL was reported to be improved/greatly improved and patient satisfaction was rated satisfied/greatly satisfied. Conclusions: For many, the application of SCS in the neck for pain after surgery is based on the obvious similarities to FBSS or anecdotal experience rather than published data. The data contained herein suggest SCS for C‐FBSS is an effective therapy that improves QoL and patient satisfaction, as well as decreasing pain and PDI. The use of successful application of neurostimulation as a therapy has largely been predicated on the principles of patient selection, implantation technique, and stimulation parameters. As such, SCS would appear to be an appropriate and valid treatment for C‐FBSS that requires further study and investigation to make additional recommendations.